Perancangan Komik Strip Tokoh Mitologi Nagagini Bertema Pandemi Di Rumah Aja - Abi Senoprabowo; Immanuel Andhika Pratama; Yumna Anindya Septiani; Ali Muqodas (AKSA: Jurnal Desain Komunikasi Visual, 2022)
This study aims to design a communication media with a pandemic theme at home in the form of a comic strip. This study uses Indonesian puppet characters as character visualizations. The method used in this study is a qualitative method. In this stage of the research process, there are stages of making a theoretical basis, data collection, brainstorming, storyboarding, rough sketches, line art, digitizing works. The purpose of making this comic strip is to urge the public, especially in Indonesia, to always stay at home and also comply with the existing health protocols during the COVID-19 pandemic.